1996
DOI: 10.1111/j.1574-6968.1996.tb08488.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and sequence of the Escherichia coli panBCD gene cluster

Abstract: A 4589 bp DNA segment containing the Escherichia coli panBCD gene cluster was sequenced, and found to contain 6 complete open reading frames. panB, panC, and panD were identified by subcloning and insertional mutagenesis. The orientation of panD was also confirmed by orientation‐specific expression of aspartate‐1‐decarboxylase. panB and panC lie adjacent to one another, but are separated from panD by orf3, which is oriented in the opposite direction. Interruptions in the remaining open reading frames did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…Lastly, the SL library contains a sequence (SL9) with 83% homology over its full length to the E. coli gene panD encoding aspartate-1-decarboxylase which catalyses synthesis of b-alanine, a precursor of both pantothenate (vitamin B 3 ) and coenzyme-A biosynthesis (Merkel and Nickols 1996). As no S. typhimurium homologs of this sequence were found in databases, it is reasonable to conclude that SL13 is a part of the S. typhimurium panD gene.…”
Section: Sequences Present In Both Genomesmentioning
confidence: 98%
“…Lastly, the SL library contains a sequence (SL9) with 83% homology over its full length to the E. coli gene panD encoding aspartate-1-decarboxylase which catalyses synthesis of b-alanine, a precursor of both pantothenate (vitamin B 3 ) and coenzyme-A biosynthesis (Merkel and Nickols 1996). As no S. typhimurium homologs of this sequence were found in databases, it is reasonable to conclude that SL13 is a part of the S. typhimurium panD gene.…”
Section: Sequences Present In Both Genomesmentioning
confidence: 98%
“…b-Alanine biosynthesis in plants is not well studied; however, in Escherichia coli the major route for b-alanine biosynthesis is via the a-decarboxylation of L-aspartate catalyzed by the panD-encoded L-aspartate-a-decarboxylase (AspDC, Williamson and Brown 1979;Merkel and Nichols 1996). This route is unique to prokaryotes and absent in eukaryotes including yeast and plants (Rathinasabapathi et al 2000;White et al 2001).…”
mentioning
confidence: 99%
“…The panC gene encodes a pantothenate synthetase (PS), which catalyzes the last step of pantothenate biosynthesis, the ATP-dependent condensation of pantoate and beta-alanine to form pantothenate. The pantothenate biosynthetic pathway has been best characterized in E. coli [56]. The crystal structure of E. coli PS was found to be a dimer from the crystal structure [57], although earlier studies indicated that it could be a tetramer in solution [58].…”
Section: Pantothenate Synthetase (Ps) the Product Of Panc (Rv3602c)mentioning
confidence: 98%